Egg Bungee Jump - Fitzgerald, Mike; Brand, Lance (Tech directions, 2011)
The goal of the problem will be twofold: (1) to observe, study, calculate, graph, and predict the elastic deformation of common rubber bands during an egg bungee jump, and (2) to bungee jump the egg as close to the floor as possible, without failure, from a height to be established by the teacher. According to Newton's first law, why and when does the egg stop moving downward? Add the distances together and divide by the number of data points. C. To determine the probable error range for your prediction point, use the average (mean) distance that you calculated above to mark the range of probable error on your graph.